Engineering Education in the Epoch of Industrial Revolution and Digital Economy - A. I. Chuchalin (Высшее образование в России)
The paper presents a review of literature and other sources of information concerning the fourth industrial revolution and the development of the digital economy. The tasks of improving the education system including higher education and engineering training are actualized. The author analyzes the development of online technologies in education, as well as blended learning, combining the advantages of traditional and online education. The paper dwells on the peculiarities of training engineers and the best practices of applying blended learning in engineering education, shows the need to optimize blended learning by maximizing the benefits of traditional and online education. A technique for using the CDIO approach, further developed for engineering education of the top levels, is proposed for the optimal blended learning design of the Bachelor, Master and PhD programs. The author adduces the concrete examples, which show the possibility of digital transformation of engineering programs with the purpose of their actualization and improving the quality of graduates’ training for complex, innovative and research engineering activity.